The RFC1 80G>A, among Common One-Carbon Polymorphisms, Relates to Survival Rate According to DNA Global Methylation in Primary Liver Cancers. - Sara Moruzzi; Silvia Udali; Andrea Ruzzenente; Alfredo Guglielmi; Patrizia Guarini; Nicola Martinelli; Simone Conci; Filippo Mazzi; Patrizia Pattini; Stephanie A Tammen; Oliviero Olivieri; Francesca Pizzolo; et al. (PLoS ONE, 2016)
Polymorphisms within one-carbon metabolism genes have been largely studied in relation to cancer risk for the function of this pathway in nucleotide synthesis and DNA methylation. Aims of this study were to explore the possible link among several common functional gene polymorphisms within one-carbon metabolism and survival rate in primary liver cancers, i.e., hepatocellular carcinoma and cholangiocarcinoma, and to assess the additional effect of global DNA methylation on survival rate and mortality risk. Forty-seven primary liver cancer patients were genotyped for ten polymorphisms: DHFR 19bp ins/del, TS 2rpt-3rpt, MTHFD1 1958G>A, MTHFR 677C>T, MTR 2756A>G, MTRR 66A>G, RFC1 80G>A, SHMT1 1420C>T, BHMT 716 A>G, TC II 776C>G. Methylation was determined in peripheral blood mononuclear cells (PBMCs) DNA as methylcytosine (mCyt) content using LC/MS/MS. Among the polymorphisms analysed, the RFC1 80G>A (rs1051266) influenced the survival rate in primary liver cancers. The RFC1 80AA was associated to a significantly reduced survival rate (22.2%) as compared to both GG and GA genotypes (61.5% and 76% respectively, p = 0.005). When the cancer patients were stratified according to the mCyt median value as high (>5.34%) or low (≤5.34%), the concomitant presence of AA genotype and low mCyt level led to a significantly worse survival rate as compared to the G allele carriership (p<0.0001) with a higher Hazard Ratio (HR = 6.62, p = 0.001). The subjects carrying the AA genotype in association with high mCyt did not show a significant difference in survival rate as compared with the G allele carriers (p = 0.919). The RFC1 80G>A polymorphism influenced the survival rate, and the presence of RFC1 80AA genotype with low global methylation in PBMCs DNA was associated with poorer prognosis and higher mortality risk, therefore highlighting novel molecular signatures potentially helpful to define prognostic markers for primary liver cancers.